2018
DOI: 10.1073/pnas.1721648115
|View full text |Cite
|
Sign up to set email alerts
|

Spatial organization and dynamics of RNase E and ribosomes inCaulobacter crescentus

Abstract: We report the dynamic spatial organization of RNase E (RNA degradosome) and ribosomal protein L1 (ribosome) using 3D single-particle tracking and superresolution microscopy. RNase E formed clusters along the central axis of the cell, while weak clusters of ribosomal protein L1 were deployed throughout the cytoplasm. These results contrast with RNase E and ribosome distribution in, where RNase E colocalizes with the cytoplasmic membrane and ribosomes accumulate in polar nucleoid-free zones. For both RNase E and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 55 publications
(78 reference statements)
0
65
0
Order By: Relevance
“…For example, inner-membrane bound ribosomes in E. coli that are actively engaged in translation (89) might play a role in specific translation of inner membrane proteins. In C. crescentus and another alpha-proteobacterium Sinorhizobium meliloti , ribosomes are detected throughout the cell including the nucleoid region (64, 90), which is different from the ribosome/nucleoid segregation observed in E. coli and B. subtilis (82, 84) . Hereby, it was suggested that, mRNA-bound ribosomal subunits show limited mobility in C. crescentus due to the observed limited dispersion of their mRNA targets from their site of transcription (64, 90, 91).…”
Section: Localized Mrna Translation and Degradationmentioning
confidence: 76%
See 2 more Smart Citations
“…For example, inner-membrane bound ribosomes in E. coli that are actively engaged in translation (89) might play a role in specific translation of inner membrane proteins. In C. crescentus and another alpha-proteobacterium Sinorhizobium meliloti , ribosomes are detected throughout the cell including the nucleoid region (64, 90), which is different from the ribosome/nucleoid segregation observed in E. coli and B. subtilis (82, 84) . Hereby, it was suggested that, mRNA-bound ribosomal subunits show limited mobility in C. crescentus due to the observed limited dispersion of their mRNA targets from their site of transcription (64, 90, 91).…”
Section: Localized Mrna Translation and Degradationmentioning
confidence: 76%
“…Hereby, the localization of RNase E clusters was found to correlate with two subcellular chromosomal positions that encode the highly expressed rRNA genes, indicating that RNase E mediated rRNA processing occurs at the site of rRNA synthesis (90). Although mediated by apparently different mechanisms compared to E. coli , the association of RNase E with DNA in C. crescentus also indicates that there is spatially organized mRNA decay in this organism.…”
Section: Localized Mrna Translation and Degradationmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been demonstrated that ExM is compatible with conventional antibodies [21,25,34] and RNA fluorescence in situ hybridization [20], therefore μExM is readily adaptable to image nanometer-scale ultrastructures in bacterial cells that are under the diffraction limit of optical imaging. Subcellular organization in bacterial cells is a field of active discovery [35], but has been so far accessible only through specialized super-resolution equipment [22,36,37]. μExM should open up new applications and provide technical convenience in this research area.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade there has been an explosion of research demonstrating the importance of selfassembling, liquid phase separated domains in both eukaryotic cells [1][2][3][4][5][6][7][8] and bacteria [9,10]. These droplets of RNA and protein, commonly referred to as 'membraneless organelles,' take advantage of liquid-liquid phase separation to achieve intracellular compartmentalization while enabling rapid exchange of their contents with the surroundings.…”
Section: Introductionmentioning
confidence: 99%